PTT-Mediated Inhibition of Cancer Proliferation and Tumor Progression by DARPin-Coated Gold Nanoparticles - Galina M. Proshkina; Elena I. Shramova; Ekaterina V. Serova; Egor A. Myachev; Aziz B. Mirkasymov; Sergey M. Deyev; Alexander B. Kotlyar (Journal of Nanotheranostics)
Targeting HER2-positive cancer cells with precision therapies is a critical challenge in oncology. Here, we present a study on gold nanoparticles (AuNPs) conjugated with DARPin_9-29, a designed ankyrin repeat protein with high specificity and affinity for HER2 receptors. In this study, we investigate the therapeutic potential of AuNP-DARPin_9-29 conjugates, which was synthesized and characterized by us earlier, for photothermal therapy (PTT). By combining AuNP-DARPin treatment with visible light illumination, we show selective inhibition of HER2-positive cancer cell proliferation and tumor progression in a murine model. The results highlight the effectiveness of AuNP-DARPin in disrupting cancer cell viability and reducing tumor growth, providing a cost-effective and targeted approach for combating HER2-positive cancers.